Demographic influences on employee perceptions: Performance management, motivation, and career advancement - Teboho Joseph Mofokeng; Karikari Amoa-Gyarteng; Shepherd Dhliwayo (Cogent Business & Management)
This study examines how demographic factors—gender, age, education, and job grade—shape employee perceptions of Employee Performance Management Systems (EPMS), work motivation, and career advancement opportunities. Using a cross-sectional comparative design, data was collected from 153 operational employees at a South African alcoholic beverage manufacturer. Findings reveal that job grade significantly influences perceptions of EPMS effectiveness, motivation, and career advancement, whereas gender, age, and education show no significant effects. The findings highlight the importance of tailoring EPMS strategies to address the unique needs of employees at different job grades, particularly in developing economy contexts.